Lipopeptide produced from Bacillus sp. W112 improves the hydrolysis of lignocellulose by specifically reducing non-productive binding of cellulases with and without CBMs - Jiawen Liu; Ning Zhu; Jinshui Yang; Yi Yang; Ruonan Wang; Liang Liu; Hongli Yuan (Biotechnology for Biofuels, 2017)
Abstract Background Surfactants have attracted increasing interest for their capability to improve the enzymatic hydrolysis of lignocellulosic biomass. Compared to chemical surfactants, biosurfactants have a broader prospect for industrial applications because they are more environmentally friendly and more effective in some researches. Commercial cellulase preparations are mainly composed of endoglucanases (EGs) and cellobiohydrolases (CBHs) that possess carbohydrate-binding modules (CBMs). However, the effects of lipopeptide-type biosurfactants on enzymatic saccharification of lignocellulose and adsorption behaviors of cellulases with CBMs remain unclear. Results In this study, we found that Bacillus sp. W112 could produce a lipopeptide-type biosurfactant from untreated biomass, such as wheat bran and Jerusalem artichoke tuber. The lipopeptide could enhance the enzymatic hydrolysis of dilute acid pretreated Giant Juncao grass (DA-GJG) by fungal and bacterial enzymes. The enhancement increased over a range of temperatures from 30 to 50 °C. Lipopeptide was shown to be more effective in promoting DA-GJG saccharification than chemical surfactants at low dosages, with a best stimulatory degree of 20.8% at 2% loading of the substrates (w/w). Lipopeptide increased the thermostability of EG and CBH in commercial cellulase cocktails. Moreover, the dual effects of lipopeptide on the adsorption behaviors of cellulases were found. It specifically lowered the non-productive binding of cellulases to lignin and increased the binding of cellulases to cellulose. In addition, we investigated the influence of lipopeptide on the adsorption behaviors of CBHs with CBMs for the first time. Our results showed that lipopeptide reduced the adsorption of CBM-deleted CBH to DA-GJG to a greater extent than that of intact CBH while the non-productive binding of intact CBH to lignin was reduced more, indicating that lipopeptide decreased the binding of CBMs onto lignin but not their combination with cellulose. Conclusions In this study, we found that lipopeptide from Bacillus sp. W112 promoted the enzymatic hydrolysis of DA-GJG at relative low loadings. The stimulatory effect could be attributed to increasing the cellulase thermostability, reducing non-productive adsorption of cellulases with CBMs caused by lignin and enhancing the binding of cellulases to cellulose.